Hospitales Renzo Piano - Fernandez-Galiano, Luis (Arquitectura viva)
Dossier dedicado a la temática. Contiene: Il miglior fabbro : Piano's Hospitals, the Story of a Box. Levitar y aliviar : Children's Hospice, Bologna (Italy). Bosque sanador : SNF General Hospital of Komotini (Greece). Cuerpos capaces : SNF Pediatric Hospital of Thessaloniki (Greece). Compromiso clínico : SNF General Hospital of Sparta (Greece). Diagnóstico urbano : Grand Paris Nord Hospital, Saint-Ouen (France). Futuro diáfano : ISMETT 2 Hospital, Carini (Italy).